The analysis of the awareness of the listeners toward sexist and misogyny message in rap music / Muhammad Ameerul Irfan Mohd Aminuddin - Mohd Aminuddin, Muhammad Ameerul Irfan (2019)
As English is second language in Malaysia, not all Malaysian are fluently writing, speaking or even understanding. The rationale conducting this research is because I want to analyse the awareness of the listeners toward hateful, sexist and misogynist lyrics in rap music. I also want to get know the relevant about the digitization of music. Using quantitative method, one hundred and eighty one respondents has been picked and answered twenty eight questions per set. From the data collected, the frequency and percentage have been analysed. How Malaysians perceived rap music has made the study achieved differently from previous study.